تقييم سلوكيات القيادة التحويلية لدى مدراء التمريض في مستشفيات التعليم العالي في مدينة اللاذقية - عليو, رلى; أخرس, غنى (Latakia University Journal -Medical Sciences Series, 2018)
Transformational leadership is a leadership style that builds commitment and creates enthusiasm and motivation for nurses in the hospital to achieve the goals set by the leader which attains the best health care for the patients. Therefore, this descriptive study was designed to evaluate the behaviors of transformational leadership among nursing managers in higher education hospitals in Lattakia ( Alasad and Tishreen university hospitals) From the point of view of 100 nurses selected by convenient sampling using a questionnaire which included the MLQ to measure transformational leadership. The results showed that the practicing level of the transformational leadership was moderate, and the most practicing behaviors were individualized consideration and idealized influence .as well as there were statistically significant differences which are according to the hospital. The study recommended the need to strengthen the practice on of transformational leadership in hospitals, and implementing induction courses and training on transformational leadership, as well as conducting similar studies on a larger scale involving more hospitals. تعتبر القيادة التحويلية نمط قيادي يبني الالتزام ويخلق الحماس والدافعية لدى الممرضين في المشفى، لبلوغ الأهداف التي يضعها القائد بما يحقق أفضل رعاية صحية للمرضى, لذلك هدفت هذه الدراسة الوصفية ذات التصميم المسحي المقطعي إلى تقييم سلوكيات القيادة التحويلية لدى مدراء التمريض في مستشفيات التعليم العالي في مدينة اللاذقية وهما مشفى الأسد وتشرين الجامعيين, من وجهة نظر 100 ممرض/ة تم اختيارهم بطريقة العينة المتاحة حيث تم توزيع استبيان القيادة متعددة العوامل (Multe Factor Leadership questionnaire) ويرمز له MLQ)) لقياس القيادة التحويلية. أظهرت النتائج البحث أن مستوى ممارسة القيادة التحويلية وحسب رأي الكادر التمريضي كانت بمستوى متوسط, وأكثر سلوكيات القيادة التحويلية ممارسة كانت الاعتبار الفردي والتأثير المثالي, كما تبين وجود فروق ذات دلالة إحصائية في آراء الكادر تبعا للمشفى الذي يعمل به, وأوصت الدراسة بضرورة تعزيز ممارسة القيادة التحويلية في المشافي, وعقد دورات تعريفية وتدريبية حول القيادة التحويلية, وإجراء دراسات مشابهة على نطاق أوسع تشمل عدد أكبر من المشافي.